On British Islam religion, law, and everyday practice in shari'a councils - Bowen, John R. (Princeton studies in Muslim politics, 2016)
On British Islam highlights British Muslims' efforts to create institutions that make sense in both Islamic and British terms. This balancing act is rarely acknowledged in Britain-or elsewhere-but it is urgent that we understand it if we are to build new ways of living together